Design, fabrication, luminescence and biomedical applications of UCNPs@mSiO2–ZnPc–CDs–P(NIPAm-MAA) nanocomposites. Issue 35 (17th August 2016) - Xu, Jiating; Yang, Dan; Lv, Ruichan; Liu, Bin; Gai, Shili; He, Fei; Li, Chunxia; Yang, Piaoping
Abstract : The NaGdF4 :Yb, Ce, Ho@NaGdF4 @mSiO2 –ZnPc–CDs–P(NIPAm-MAA)–DOX platform exhibits excellent anti-tumor efficacy due to synergistic PDT, PTT and chemotherapy, accompanied by multimodal imaging properties. Abstract : A nanoplatform capable of pH/thermo-coupling sensitive drug release, multimodal imaging, and synergetic antitumor therapy was designed and prepared. The core–shell structured platform consists of a dominant red up-converted luminescence (UCL) core and a copolymer P(NIPAm-MAA) gated mesoporous silica layer with functional cargos loaded inside. Due to the tri-doped Yb/Ce/Ho ions in the core and the inert shell coating, the nanoparticles show intense red UCL under NIR laser excitation. Thereafter, the emitted red light transfers energy to the conjugated photodynamic therapy (PDT) agent zinc(ii )-phthalocyanine (ZnPc), which produces singlet oxygen, and the decorated carbon dots (CDs) generate an obvious photothermal effect upon 980 nm laser irradiation as well as avoiding ZnPc leakage. Notably, the thermal effect together with the acidic environment in the cancer sites induces the shrinkage of P(NIPAm-MAA), realizing targeted and controllable release of DOX. Due to the photothermal-/photodynamic-/chemo-therapy derived synergistic effect, the nanoplatform exhibits desirable tumor inhibition efficacy, as verified by both in vitro and in vivo results. In particular, the doped rare earth ions enable the product to have simultaneous UCL, magnetic resonance imaging (MRI) and computed tomography (CT) imaging properties, thus achieving the integration of diagnosis and therapy.